ANALYSIS OF SERVICE QUALITY ON OUTPATIENT PATIENT SATISFACTION: LITERATURE REVIEW - Prawira, Ricky; Saputra, Dikki (Department of Nursing, Faculty of Medicine, Universitas Tanjungpura, 2025)
Background: Healthcare quality is an essential pillar of modern healthcare systems, directly impacting patient satisfaction. This article comprehensively analyzes the influence of the service quality dimension on outpatient satisfaction in hospitals. Through a systematic literature review of various international studies, it was found that there is a strong positive relationship between patient-perceived service quality and their satisfaction levels. The SERVQUAL model, with its five dimensions (tangibles, consent, responsiveness, assurance, and empathy), has proven to be a dominant framework for improving shared care. However, patient perceptions of these dimensions vary contextually, with a combination of expectations and perceptions being the primary drivers of dissatisfaction. Long waiting times and ineffective communication also significantly impact patient satisfaction. Therefore, improving service quality requires a holistic approach that focuses not only on technical improvements but also on managing patient expectations, enhancing staff communication skills, optimizing administrative processes, and addressing staff well-being. Recommendations include the implementation of digital systems, patient-centered training, and information transparency to create a more satisfying outpatient experience and foster patient loyalty.